PROBLEMATIKA MANHAJ TAKFIR MUHAMMAD BIN ABDUL WAHHAB (TELAAH KRITIS DALAM TINJAUAN MASLAHAH) - Alwi Bani Rakhman (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2020)
Muhammad bin Abdul Wahhab is one of Muslims group leader who promoted the takfir concept as an important part in his religious thought. This article explains his methodology of takfir and its legal implications, then examined critically by using maslahah perpective. This study of the works of Muhammad ibn Abdul Wahhab concludes: First, the methodology of takfir Muhammad bin Abdul Wahhab can be seen through understanding his principle thoughts about Ibadah (worship) and Islam, and also various rules that must be known and implemented related to when takfir can be implemented, such as the terms and barriers of takfir, qiyam al-hujjah dan masa’il zahirah dan masa’il khafiyyah. Second, considering the legal implications of takfir, then at that time his concept doesn’t fully lead to maslahah ‘a>mmah primarily related to the variety of methods of understanding religion (al-Qur’an and al-Sunnah).